The association between office design and employee’s productivity at Seri Alam Properties Sdn Bhd (UMLAND) / Iffah Aliah Mohd Nasir - Mohd Nasir, Iffah Aliah (Faculty of Office Management and Technology, 2016)
This study was conducted to explain the association between office design and employee’s productivity. The subject area for this study is Seri Alam Properties Sdn Bhd (UMLAND) in measuring the impact of office design towards employee’s productivity, the researcher decided to use furniture, noise, temperature, lighting and spatial arrangements the main elements that influence employee’s productivity as the result to the employees in Seri Alam Properties Sdn Bhd (UMLAND).